BDNF LEVEL IN THE BLOOD OF PATIENTS WITH ANKYLOSING SPONDYLITIS COMORBID WITH ALEXITHYMIA, ITS CORRELATION WITH CLINICAL COURSE AND TREATMENT EFFICACY - Vasylets, Viktoria; Stanislavchuk, Mykola (Eastern Ukrainian Medical Journal, 2025)
Introduction. The treatment of ankylosing spondylitis is a complex and still unresolved problem due to the complexity and polymorphism of pathogenetic mechanisms and the variability of the clinical course. One of the important factors modifying the clinical course and resistance to treatment is alexithymia. A promising way to develop new approaches to the treatment of ankylosing spondylitis is to study the role of BDNF in pathogenesis, clinical manifestations, and resistance to therapy. The objective of this study was to examine BDNF levels in the blood of patients with ankylosing spondylitis comorbid with alexithymia, as well as its correlation with the clinical course and treatment efficacy. Materials and Methods. 127 patients with ankylosing spondylitis were examined using the BASDAI, ASDAS, BASFI, BASMI, HAQ, ASAS HI/EF, BAS-G, ASQoL, MAF, PSQI, HAM-D, and MMSE scales; alexithymia was determined using the Ukrainian TAS-20 adapted version. The level of BDNF in blood plasma was determined by enzyme-linked immunosorbent assay. Results. Patients with AS have been found to have higher levels of BDNF compared to healthy individuals: 273.13±69.58 pg/ml versus 160.40±61.08 pg/ml (p<0.001). Patients with elevated BDNF levels in the blood (above the median) had significantly higher disease activity indicators: ESR – 37.03±22.19 mm/h vs. 22.13±14.29 mm/h (p<0.01); BASDAI – 6.97±1.73 points vs. 5.42±2.00 points (p<0.01); ASDAS-ESR – 4.04±0.83 points vs. 3.31±0.75 points (p<0.001); functional capacity of patients by BASMI – 5.19±2.13 points vs. 3.84±1.83 points (p<0.05); BAS-G – 7.44±1.78 points vs. 5.88±2.01 points (p<0.01). In these patients, the ASAS HI index was 10.53±3.13 points versus 8.84±3.56 points (p<0.05); ASAS EF – 4.22±1.50 points versus 3.22±1.34 points (p<0.05); there were also higher TAS-20 indicators: 61.22±8.06 points versus 56.19±9.01 points (p<0.05). In patients with no alexithymia, BDNF levels were lower compared to patients with possible alexithymia: 222.50±60.10 pg/ml versus 275.93±21.10 pg/ml; while in patients with alexithymia, BDNF levels were higher than in patients of these groups: 286.08±82.75 pg/ml. ASAS-20 responders had lower BDNF levels compared to non-responders: 236.43±59.01 pg/ml versus 285.37±69.04 pg/ml (p<0.05). Conclusions. In patients with ankylosing spondylitis, there is an increase in blood BDNF levels. Alexithymic traits are associated with higher levels of BDNF in the blood, which indicates the possible involvement of BDNF in the pathogenetic mechanisms of alexithymia formation. Elevated BDNF levels are associated with a worse clinical course of ankylosing spondylitis and are a predictor of treatment resistance.